REPRESENTATION OF EXISTENTIAL FEMINISM IN THE LYRIC OF ‘I MADE YOU LOOK’ SONG BY MEGHAN TRAINOR - Indah Lestari; Erna Pranata Putri; Dwi Nitisari (Asosiasi Dosen Muda Indonesia, 2022)
This is a descriptive qualitative study that aims to describe how existential feminism is represented in the lyrics of a popular song entitled 'I made you look' sung by Meghan Trainor. Lyrics are a series of related poems in which some sort of broad narrative is tantalizingly offered (Culler, 2017). The aims of the research are 1) to find out the meaning of the lyric of ‘I made you look’ song and 2) to describe the existential-feminism represented in the lyric of ‘I made you look’ songThe method used in this research is descriptive with the approach of syntagmatic and paradigmatic relation by Ferdinand de Saussure (1983) and the theory of existential feminism by Beauvoir (1949). The results obtained are from the 5 stanzas of the lyrics, there are phrases containing existential feminism that is being self-confidence about femaleness, about sexual roles, about community, and about body.